2018
DOI: 10.1007/s11262-018-1546-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process

Abstract: Human parainfluenza virus type 3 (hPIV3) is an important respiratory pathogen that causes the majority of viral pneumonia of infants and young children. hPIV3 can infect host cells through the synergistic action of hemagglutinin-neuraminidase (HN) protein and the homotypic fusion (F) protein on the viral surface. HN protein plays a variety of roles during the virus invasion process, such as promoting viral particles to bind to receptors, cleaving sialic acid, and activating the F protein. Crystal structure res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…HN protein is a homotetrameric type II integral membrane protein consisting of a cytoplasmic domain, transmembrane domain, helical stalk, and globular head (37). Three functions of the HN protein have been identified so far: 1) hemagglutinin activity for receptor binding, 2) neuraminidase activity for receptor cleavage by hydrolyzing sialic acid residues, and 3) fusion activation that interacts with the F protein (38). HN and F proteins work in tandem to infect the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…HN protein is a homotetrameric type II integral membrane protein consisting of a cytoplasmic domain, transmembrane domain, helical stalk, and globular head (37). Three functions of the HN protein have been identified so far: 1) hemagglutinin activity for receptor binding, 2) neuraminidase activity for receptor cleavage by hydrolyzing sialic acid residues, and 3) fusion activation that interacts with the F protein (38). HN and F proteins work in tandem to infect the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…The A22T and K31N mutations do not belong to the stalk, globular, or F-specific regions. Although we could not determine whether these mutations can significantly affect the infectivity of HPIV3 or alter the structure of proteins, further research is needed, as certain mutations have been reported to have a significant effect on viral activity (38).…”
Section: Discussionmentioning
confidence: 99%
“…It has a short N-terminal cytoplasmic tail, transmembrane domain, stalk region and C-terminal six-bladed β-propeller head domain typical of sialidases, which contains the catalytic site. The HN catalytic site functions both in sialoglycan receptor binding and cleavage [17][18][19]. The stalk domain of HN physically interacts with the F protein and plays a role in triggering the F protein rearrangements leading to membrane fusion [15].…”
Section: Introductionmentioning
confidence: 99%